Environmental impact assessment for nanotechnologies: integrating the ecological and the chemical perspective. (1st January 2014) - Filser, Juliane; Köser, Jan
The development and application of products containing engineered nanoparticles (ENP) has dramatically increased over the past decade, whereas the assessment of potential hazards to humans and especially to the environment substantially falls behind. The UFT Centre for Environmental Research and Sustainable Technology at the University of Bremen focuses on environmentally benign nanomaterials. Here we present some results from two ongoing large project networks. Using examples from ecotoxicological tests and numerical speciation we demonstrate the necessity of interdisciplinary cooperation for the hazard assessment of silver nanoparticles.